Data base of Nitrous oxide emissions from Urine patches in LAC - Latin America Greenhouse Gas Mitigation Network (International Center for Tropical Agriculture, 2017)
This database contains data obtained from measurements of nitrous oxide from urine patches on improved and degraded pastures in five countries in LAC (Colombia, Argentina, Nicaragua, Brazil and Trinidad & Tobago). Specifically, the data is on N2O fluxes, soil proprieties, nitrogen content in urine and soil nitrogen. In addition, we include data on N2O emission factors in each country.